2022
DOI: 10.1200/jco.2022.40.16_suppl.e12500
|View full text |Cite
|
Sign up to set email alerts
|

Body composition changes in a 12-week exercise intervention for breast cancer patients.

Abstract: e12500 Background: Evidence has linked weight gain and obesity to increased breast cancer risk, poorer outcomes, decreased survivorship, and increased risk of recurrence. Adjuvant therapies can increase weight gain, making tailored exercise interventions beneficial in maintaining a healthy weight. In this study, body composition changes were examined after a 12-week exercise program in a cohort of breast cancer survivors. Methods: The Breast Cancer Exercise Rehabilitation Research Study recruited breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…This study demonstrated that a tailored exercise intervention given to IBC in a real-world setting improved aerobic fitness, body composition, lower limb endurance, physical activity behaviour, depression status, physical wellbeing, and fatigue status. Similar to earlier work, this study demonstrated that exercise improves aerobic fitness [36], body composition [37], lower limb muscular endurance [38], physical activity behaviour [39], and decreases IBC fatigue [2,5,6] and depression [40]. This study suggests that similar benefits from exercise can be attained in a real-world setting.…”
Section: Discussionsupporting
confidence: 88%
“…This study demonstrated that a tailored exercise intervention given to IBC in a real-world setting improved aerobic fitness, body composition, lower limb endurance, physical activity behaviour, depression status, physical wellbeing, and fatigue status. Similar to earlier work, this study demonstrated that exercise improves aerobic fitness [36], body composition [37], lower limb muscular endurance [38], physical activity behaviour [39], and decreases IBC fatigue [2,5,6] and depression [40]. This study suggests that similar benefits from exercise can be attained in a real-world setting.…”
Section: Discussionsupporting
confidence: 88%